The ambassador of Nowhere, Texas - Holt, Kimberly Willis (Square Fish : Henry Holt and Company, 2022)
In 2001, seventh-grader Rylee Wilson and new student Joe, whose father was a New York City first responder on 9/11, decide to find Zachary Beaver and reunite him with Rylee's father, Toby.